2016
DOI: 10.1016/j.jnucmat.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The function of Sn(II)-apatite as a Tc immobilizing agent

Abstract: At the U.S. Department of Energy Hanford Site, Tc-99 is a component of lowactivity waste (LAW) fractions of the nuclear tank waste and removal of Tc from LAW streams would greatly benefit the site remediation process. In this study, we investigated the removal of Tc(VII), as pertechnetate, from deionized water (DIW) and a LAW simulant through batch sorption testing and solid phase characterization using tin (II) apatite (Sn-A) and SnCl2. Sn-A showed higher levels of Tc removal from both DIW and LAW simulant. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…chromate, Cr(VI) 2 O 7 2-, and nitrate/nitrite, NO 3 -/NO 2 -). Examples of this include the decrease in Tc removal capability observed for many compounds such as Sn(II)-treated apatite, zerovalent Fe and others in simulated low activity waste (LAW) or low level waste (LLW) (Darab et al 2007;Qafoku et al 2014;Asmussen et al 2016). Despite this, Fe-sulfides have been suggested as possible treatments for Tc containing nuclear wastes (Watson and Ellwood 2003) and recent work has shown that sulfide based materials are adept at sequestering Tc from LAW.…”
Section: Technetium Sulfide In Waste Formsmentioning
confidence: 99%
“…chromate, Cr(VI) 2 O 7 2-, and nitrate/nitrite, NO 3 -/NO 2 -). Examples of this include the decrease in Tc removal capability observed for many compounds such as Sn(II)-treated apatite, zerovalent Fe and others in simulated low activity waste (LAW) or low level waste (LLW) (Darab et al 2007;Qafoku et al 2014;Asmussen et al 2016). Despite this, Fe-sulfides have been suggested as possible treatments for Tc containing nuclear wastes (Watson and Ellwood 2003) and recent work has shown that sulfide based materials are adept at sequestering Tc from LAW.…”
Section: Technetium Sulfide In Waste Formsmentioning
confidence: 99%
“…The reduction of 99-Tc from its soluble Tc(VII)O 4 form to a low solubility Tc(IV) species can be utilized to extract 99-Tc from liquid waste streams (Serne et al 2016a). Several candidate reductants exist which can drive the reaction of Tc(VII) including Sn(II) (Asmussen et al 2016b;Duncan et al 2016;Taylor-Pashow et al 2018), Fe (0 or II) (Del Cul et al 1995) and S(0) (Pearce et al 2018). In this approach a simple chemical form of the reductant would be introduced to the LAW to precipitate 99-Tc.…”
Section: Line 6 -Redox Strike/co-precipitationmentioning
confidence: 99%
“…The primary challenges with the approach are the presence of excess Cr(VI) in the LAW (along with other oxidants such as NO 3 ) that would compete for reductants (~50 × higher than 99-Tc), decreased efficiency of some reductants in alkaline conditions (Asmussen et al 2016b), and the potential need for a filtration step to collect the precipitated 99-Tc. The strike could be performed as a direct chemical addition or in a column.…”
Section: Line 6 -Redox Strike/co-precipitationmentioning
confidence: 99%
“…Granular activated carbon (GAC; Nuchar WV-G) from West Virginia Pulp and Paper was evaluated for TcO4removal from groundwater, but the available data demonstrated that its adsorption capacity was low [8]. For high TcO4waste streams, reductant materials (i.e., Fe sulfides [9,10], layered potassium metal sulfides [11], tin-apatite [12], adsorbed or structural Fe(II) [13][14][15][16][17], zero valent iron [18]), and reducing bacteria [9,10,19] can chemically reduce Tc(VII) to sparingly soluble Tc(IV). However, the solubility of the precipitated reduction product, Tc(IV)O2•1.6H2O, is still relatively high (i.e., 1.5×10 -8 M) in groundwater [20,21], greatly exceeding the EPA's maximum contaminant level (MCL) of 5×10 -10 M Tc.…”
Section: Introductionmentioning
confidence: 99%